Democracy and Bureaucracy: A Bibliometrics Comparative Analysis on the Developed and Developing Countries - Meiyani, Eliza; Putri Sadayi, Delila; Hayan Mochammad, Fadhil (International Journal of Social Science, Education, Communication and Economics, 2025)
This study aims to analyze the development of democratic and bureaucratic theories that occur in developed and developing countries. The author identifies this research by analyzing journal articles that are indexed by Scopus as journals with reputable and accountable research outputs. The Scopus database was used as data in this study. This study uses a comparative qualitative method of analysis by comparing documents published in developed and developing countries. The results of this study show that; 1) The development of research related to democracy and bureaucracy based on the Scopus database has decreased significantly in 2017-2020, increased in 2021 and decreased again in 2022. 2) The predominance of research related to democracy and bureaucracy occurs in the United State, where the country is a full-fledged democracy. 3) The connectedness of the study during 2015-2022 is divided into 8 clusters, each cluster displays a comparison of countries with the interconnectedness between countries involved in the research. 4) The high weberianess of the state bureaucracy is due to the professional public administration before democracy combined with electoral competition and non-ethnic politics. Brazil, South Korea, and Taiwan are examples. Argentine hyper-presidentialism exacerbates top-down politicization of public administration and personalist patronage.